2022
DOI: 10.3390/jcm11175228
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Arterial Pressure of Oxygen and Carbon Dioxide in Patients Supported by Veno-Arterial ECMO

Abstract: Background: The present study aimed to assess the determinants of arterial partial pressure of oxygen (PaO2) and carbon dioxide (PaCO2) in the early phase of veno-arterial extracorporeal membrane oxygenation (VA ECMO) support. Even though the guidelines considered both the risks of hypoxemia and hyperoxemia during ECMO support, there are a lack of data concerning the patients supported by VA ECMO. Methods: This is a retrospective, monocentric, observational cohort study in a university-affiliated cardiac inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Theoretically, further administrating fluid to preload-independent patients potentially prompts fluid overload and congestion, which are well-known clinical conditions characterized by sympathetic stress and reninangiotensin system activation, thereby resulting in an increased trend of Ea. Moreover, two studies reversely verified the negative impact of fluid expansion on the Ea in this cohort population: decongestive therapy using diuretics reduced the Ea and improved the VAC in congestive patients (10,11). Accordingly, the fluid-induced changes in the Ea, rather than the Ees, seem to be the primary determinant of fluid-induced VAC changes.…”
Section: Discussionmentioning
confidence: 66%
“…Theoretically, further administrating fluid to preload-independent patients potentially prompts fluid overload and congestion, which are well-known clinical conditions characterized by sympathetic stress and reninangiotensin system activation, thereby resulting in an increased trend of Ea. Moreover, two studies reversely verified the negative impact of fluid expansion on the Ea in this cohort population: decongestive therapy using diuretics reduced the Ea and improved the VAC in congestive patients (10,11). Accordingly, the fluid-induced changes in the Ea, rather than the Ees, seem to be the primary determinant of fluid-induced VAC changes.…”
Section: Discussionmentioning
confidence: 66%
“…They found that median P POST O 2 decreased from 301 [215–386] mmHg at baseline, to 140 [78–220] mmHg at H48. In this study, only one third of P POST O 2 values were below 150 mmHg [ 20 ]. A possible reason for this tolerance with hyperoxemia might be the fear of unrecognized hypoxemia of the lower part of the body.…”
Section: Discussionmentioning
confidence: 96%
“…Most of studies report either only punctual F S O 2 values [ 17 , 18 ], or protocol for the initial F S O 2 setting [ 1 , 2 , 5 , 6 , 19 ]. In a retrospective monocentric study on 54 patients, median F S O 2 decreased from 80% [70–100] at baseline, to 70% [65–80] at 48 h [ 20 ]. In another study, mean F S O 2 was around 80% between day 1 and day 10 of ECMO support [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the primary determinant of D o 2 (via ECMO circuit) is the ECMO blood flow rate (27, 38, 39, 47, 48). When ECMO blood flow (L/min) is increased, D o 2 increases proportionately (Equation 1).…”
Section: The Determinants Of Oxygenation and Circuit Physiologymentioning
confidence: 99%
“…The determinants of oxygenation during venoarterial ECMO are complex, largely due to the interaction between the circuit physiology and dynamic patient factors described above (48, 60). As such, the assessment and interpretation of oxygen exposure is challenging given that it may vary across body regions, and varies with different phases of the patients’ illness (25).…”
Section: A Suggested Approachmentioning
confidence: 99%